Strategic Engagement of Technical Surge Capacity for Intensified Polio Eradication Initiative in Nigeria, 2012–2015. (2nd April 2016) - Yehualashet, Yared G.; Mkanda, Pascal; Gasasira, Alex; Erbeto, Tesfaye; Onimisi, Anthony; Horton, Janet; Banda, Richard; Tegegn, Sisay G.; Ahmed, Haruna; Afolabi, Oluwole; Wadda, Alieu; Vaz, Rui G.; et al.
Abstract : Background. Following the 65th World Health Assembly (WHA) resolution on intensification of the Global Poliomyelitis Eradication Initiative (GPEI), the Nigerian government, with support from the World Health Organization (WHO) and other partners, implemented a number of innovative strategies to curb the transmission of wild poliovirus (WPV) in the country. One of the innovations successfully implemented since mid 2012 is the WHO's engagement of surge capacity personnel. Methods. The WHO reorganized its functional structure, adopted a transparent recruitment and deployment process, provided focused technical and management training, and applied systematic accountability framework to successfully manage the surge capacity project in close collaboration with the national counterparts and partners. The deployment of the surge capacity personnel was guided by operational and technical requirement analysis. Results. Over 2200 personnel were engaged, of whom 92% were strategically deployed in 11 states classified as high risk on the basis of epidemiological risk analysis and compromised security. These additional personnel were directly engaged in efforts aimed at improving the performance of polio surveillance, vaccination campaigns, increased routine immunization outreach sessions, and strengthening partnership with key stakeholders at the operational level, including community-based organizations. Discussion. Programmatic interventions were sustained in states in which security was compromised and the risk of polio was high, partly owing to the presence of the surge capacity personnel, who are engaged from the local community. Since mid-2012, significant programmatic progress was registered in the areas of polio supplementary immunization activities, acute flaccid paralysis surveillance, and routine immunization with the support of the surge capacity personnel. As of 19 June 2015, the last case of WPV was reported on 24 July 2014. The surge infrastructure has also been instrumental in building local capacity; supporting other public health emergencies, such as the Ebola outbreak response and measles and meningitis outbreaks; and strengthening the integrated disease surveillance and response. Due to weak health systems in the country, it is vital to maintain a reasonable level of the surge capacity for successful implementation of the 2013–2018 global polio endgame strategy and beyond.